Cross-border services trade and regulation: Evidence from the European architectural sector - Oliver Arentz; Larissa Hages; Clemens Recker (Otto-Wolff-Institut für Wirtschaftsordnung (owiwo), 2018)
In this research project we analyse to what extend differences in national regulations are actually a barrier to cross-border trade in architectural services in the single market. This question appears to be interesting for two main reasons: Firstly, the comparable low level of cross-border trade in architectural services in the internal market raises the question of causes and possible simplifications. Secondly, other research with a different geographic scope suggests a possible link between less uniform or very restrictive professional regulation and a low volume of cross-border trade in the case of many regulated professions. In order to capture the respective national regulatory levels and possible national differences, these academic research uses indicators such as the OECD "Services Trade Restrictiveness Index for cross-border trade in services" (OECD-STRI). In this project, we base our research directly on the academic research mentioned above. We analyse whether these findings also apply to trade in architectural services in the European internal market. If we use the OECD-STRI for architectural services, we find no empirical connection between a higher homogeneity of regulation and more cross-border trade in architectural services. Neither do we find any correlation between lower, supposedly trade-friendly OECD-STRI index values of the respective trading partners and a higher volume in intra-EU trade in architectural services.
Keywords: 330